Do Wage Spillovers Lead to Labor Productivity Spillovers? - Joko Susanto; Didit Welly Udjianto (Signifikan: Jurnal Ilmu Ekonomi, 2020)
This research wants to analyze wage spillovers in Yogyakarta and Central Java, and whether these spillovers induce labor productivity spillovers. This study uses data published by the Central Bureau of Statistics (BPS) and includes wage rate, regency/city minimum wage, capital intensity, education level, growth, and labor productivity. The spatial regression is using in this study. The results show that there is a wage spillover across regencies/municipalities in Yogyakarta and Central Java. The wage rate is not only influenced by the variables in the area but is also by the wage rates in the surrounding area. However, these wage spillovers do not encourage labor productivity spillovers. The labor productivity in a regency/city depends on the availability of physical capital in this area. An expansion in labor productivity in a zone does not affect the increment in labor productivity in the encompassing zone. The physical capital not easily moved between regencies/cities.JEL Classification: J24, J3, J61,  How to Cite:Susanto, J., & Udjianto, D. W. (2020). Do Wage Spillovers Lead to Labor Productivity Spillovers? Signifikan: Jurnal Ilmu Ekonomi, Vol. 9(1), 51-68. doi: http://dx.doi.org/10.15408/sjie.v9i1.12903.